Juvenile Treatment Model according to Juvenile Criminal Justice System in the LPKA (Juvenile Detention Center) Class I, Tanjung Gusta, Medan (Medico Legal Update, 2020)
Law No. 11/2012 on the Juvenile Criminal Justice System states that child prisoners in the LPKA (JuvenileDetention Center) are required to participate in the treatment program which consists of personal treatmentand independency treatment so that they can come back to their communities well; besides that, they havebeen prepared with skills. The research problem was how about the treatment model of juveniles who havecommitted criminal offenses in the LPKA Class 1, Tanjung Gusta, Medan. It is expected that through thisresearch a treatment model of juveniles who have committed criminal offenses in the LPKA can be foundin the future. The research used normative and empirical approaches. The data were gathered by conductinginterviews with some informants in the Section of Juvenile Treatment of the LPKA Class 1, TanjungGusta, Medan, and with the child prisoners. The result of the research showed that personal treatment andindependency treatment in the LPKA Class 1, Tanjung Gusta, Medan, were performed with group (classial)and scheduled treatment models. It is recommended that individual treatment model, especially independencytreatment be used in the future, and personal treatment should be done by using classial treatment model.